POSYANDU REMAJA PEMEGANG UTAMA KESEHATAN REPRODUKSI BAGI REMAJA DESA SENDANGAGUNG - Ratnawati, Riska; Utami, Yeni; Prabawati, Pangestu; Oktaviana, Melli (Universitas Respati Yogyakarta, 2021)
Community service activities are carried out in the Sendangagung village in Magetan Regency, East Java. Sendangagung Village has quite a number of teenagers so that the health workers in it with a set of villages make a program called Integrate Health Care Young which is relatively new and quite interesting. This activity aims to increase education and insight of adolescents in the field of health as a whole, especially reproductive health. Activities included examining TB, BB, blood pressure, giving Fe tablets to young women and promoting reproductive health. In these activities, youth also had the opportunity to become cadres to help smooth the administration and data collection of theÂ Integrated Health care center results.Â Keywords: Integrated Health Care Young, Reproductive Health, Young